2022
DOI: 10.2147/opth.s342965
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Compliance with Diabetic Retinopathy Screening: A Qualitative Study Comparing English and Spanish Speakers

Abstract: The purpose of this study was to understand individual-, social-, and system-level factors that affect compliance with recommended diabetic retinopathy (DR)-evaluations, and how these factors vary between English and Spanish speakers. Patients and Methods:We conducted a qualitative study using semi-structured interviews. Study subjects included Kaiser Permanente Southern California members with type II diabetes mellitus at least aged 26 years who spoke English or Spanish. Patients were divided into groups base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Similarly, Owsley et al reported that transportation, trusting the physician, and communicating with the physician were perceived barriers to care for African American individuals. Hispanic individuals with diabetes are also more likely to face language barriers and struggles with health care costs . In previous studies, as well as in ours, the quality of communication with the physician was a key factor.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Similarly, Owsley et al reported that transportation, trusting the physician, and communicating with the physician were perceived barriers to care for African American individuals. Hispanic individuals with diabetes are also more likely to face language barriers and struggles with health care costs . In previous studies, as well as in ours, the quality of communication with the physician was a key factor.…”
Section: Discussionsupporting
confidence: 48%
“…Hispanic individuals with diabetes are also more likely to face language barriers and struggles with health care costs . In previous studies, as well as in ours, the quality of communication with the physician was a key factor. Our results demonstrated the importance of practitioner concordance in relation to delaying eye care, suggesting the potential importance of enhancing workforce diversity and implementing cultural competency training to bridge the gap between patient-physician discordance …”
Section: Discussionmentioning
confidence: 71%
“…These results highlight the importance of continuity nursing based on the 4C model in improving daily quality of life and gaining patient recognition, consistent with the continuity nursing theory proposed by Boucher et al [22,23] Previous studies by Boucher Marie Carole et al have also demonstrated that nursing models can improve patient compliance, enhance patient quality of life, and ultimately improve patient recovery after surgery. [23,24] This study fills knowledge gaps in the existing literature and provides an important theoretical and practical foundation for further research in this field. It is of significant importance for improving patient treatment outcomes and quality of life, reducing complication rates, and enhancing overall patient health.…”
Section: Groupmentioning
confidence: 72%
“…These results highlight the importance of continuity nursing based on the 4C model in improving daily quality of life and gaining patient recognition, consistent with the continuity nursing theory proposed by Boucher et al [ 22 , 23 ] Previous studies by Boucher Marie Carole et al have also demonstrated that nursing models can improve patient compliance, enhance patient quality of life, and ultimately improve patient recovery after surgery. [ 23 , 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…A prior study showed that Spanish-speaking patients experienced difficulty communicating with eye care professionals in diabetic retinopathy evaluations. 26 These challenges and other unmeasured variables, such as level of education, literacy, or perceptions of implicit bias, may create additional barriers for Spanish-speaking patients receiving a recommendation to schedule an inperson DFE with an ophthalmologist. [27][28][29] For example, low disease knowledge has been identified as an important Clinical Ophthalmology 2022:16 https://doi.org/10.2147/OPTH.S380629 DovePress 3027 barrier to follow-up in patients with chronic eye diseases, 30 and may contribute to low adherence to follow-up appointments after teleretinal screening as well.…”
Section: Discussionmentioning
confidence: 99%